Charles Bonnet syndrome - Stojanov, Oliver (Vojnosanitetski pregled, 2017)
Introduction. Charles Bonnet syndrome (CBS) is a condition that causes visual hallucinations in patients without any mental illnesses. CBS is characterized by the presence of vivid, complex and recurrent visual hallucinations, and do not occur in the setting or as part of delirium or other psychological illnesses. The condition is present in patients who have visual loss due to age-related macular degeneration (AMD), cataracts and/or other ocular diseases that influence vision. Case report. A 81-year-od woman reported to ophthalmologist complaining of visual hallucinations that consisted of white pigeons. Hallucinations were present for two years and she was well aware that hallucinations were unreal. Mental illnesses were excluded by the psychiatrist. Complete ophthalmologic examination was performed, and finding revealed visual acuity of 0.3 (right eye) and 0.5 (left eye), in both eyes cataracts and AMD (wet form). Optical coherence tomography confirmed the fundoscopic finding of AMD. The patient rejected treatment of cataracts and AMD due to old age, and hallucinations persisted. Conclusion. CBS should be considered in patients with visual hallucinations and ocular diseases that influence vision. It is essential to distinguish CBS from mental illnesses, since patients with CBS are fully aware that hallucinations are not real. Awareness of CBS could help physicians upon referring patients to ophthalmologists instead of psychiatrists, and therefore avoid patients being misdiagnosed.